Understanding consumer animosity in an international crisis: nature, antecedents, and consequences - Leong, Siew Meng; Cote, Joseph A; Ang, Swee Hoon; Tan, Soo Jiuan; Jung, Kwon; Kau, Ah Keng; Pornpitakpan, Chanthika (Journal of International Business Studies, 2008)
The nature, antecedents, and consequences of consumer animosity during the 1997 Asian economic crisis are investigated, based on a large-scale survey of 2000 adult consumers representative of five affected nations (Indonesia, Malaysia, Singapore, South Korea, and Thailand). An animosity model was developed and tested with the US and Japan as target countries. As predicted, stable and situational animosity reduced willingness to buy products from a perceived hostile national entity. Affective evaluations and cognitive judgments were negatively influenced by situational animosity but not by stable animosity. As expected, situational animosity was increased by external attribution, perceived external control, and stable animosity. Implications of these findings are discussed, and directions for future research suggested.